Morphology, phylogeography, phylogeny, and taxonomy of Cyclorhiza (Apiaceae) - Song, Bo-Ni; Aou, Xueyimu; Tian, Rong-Ming; Cai, Jing; Tan, Wei-Yan; Liu, Chang-Kun; He, Xing-Jin; Zhou, Song-Dong (Frontiers in Plant Science, 2025)
BackgroundThe genus Cyclorhiza is endemic to China and belongs to the Apiaceae family, which is widely distributed in the Himalaya–Hengduan Mountains (HHM) region. However, its morphology, phylogeny, phylogeography, taxonomy, and evolutionary history were not investigated due to insufficient sampling and lack of population sampling and plastome data. Additionally, we found that Seseli purpureovaginatum was not similar to Seseli members but resembled Cyclorhiza species in morphology, indicating that the taxonomic position of S. purpureovaginatum needs to be re-evaluated.MethodsFirst, we observed the morphology of the genus. Second, we newly sequenced four plastomes and conducted comparative analyses. Third, we used the newly sequenced internal transcribed spacer (ITS) and chloroplast DNA (cpDNA) (matK, trnQ-rps16, and trnD-trnT) from 27 populations totaling 244 individuals to explore the genetic diversity and structure. Finally, we performed the phylogenetic analyses based on three datasets (plastome data, ITS sequences, and haplotypes) and estimated the origin and divergence time of the genus.Results and discussionThe morphology of Cyclorhiza plants and S. purpureovaginatum was highly similar, and their plastomes in structure and features were conserved. The genus possessed high genetic diversity and significant lineage geographic structure, which may be associated with the long-term evolutionary history, complex terrain and habitat, and its sexual reproduction mode. The genus Cyclorhiza originated in the late Eocene (36.03 Ma), which was closely related to the early uplift of the Qinghai–Tibetan Plateau (QTP) and Hengduan Mountains (HDM). The diversification of the genus occurred in the late Oligocene (25.43 Ma), which was largely influenced by the colonization of the newly available climate and terrain. The phylogenetic results showed that Cyclorhiza species clustered into a separate clade and S. purpureovaginatum nested within Cyclorhiza. Cyclorhiza waltonii was sister to Cyclorhiza peucedanifolia, and Cyclorhiza puana clustered with S. purpureovaginatum. Thus, based on the morphology, plastome analyses, and phylogenetic evidence, S. purpureovaginatum should be transferred to Cyclorhiza. All these evidences further supported the monophyly of the genus after including S. purpureovaginatum. Finally, we clarified the generic limits of Cyclorhiza and provided a species classification key index for the genus. In conclusion, the study comprehensively investigated the morphology, phylogeography, phylogeny, taxonomy, and evolution of the genus Cyclorhiza for the first time.